Implementasi Pelatihan Bilal Jenazah Dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 3 Karang Raja - Kurniawan, Paga; Nurlailah, Nurlailah; Valensi, Devy; Agustini, Evaliani; Ramdhan, Akmal; Rusmin, Rusmin; Shofiah, Robiatun; Putra, Deni; Hidayatullah, M Rizki; Dahirin, Dahirin (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: This study aims to analyze the implementation of bilal jenazah (funeral prayer leader) training in Islamic Education (PAI) learning at SMP Negeri 3 Karang Raja. The research uses a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews with PAI teachers and students, as well as documentation of religious activities. Data analysis techniques involve data collection, data presentation, verification, and drawing conclusions. Data validity was checked through triangulation. The results and discussion indicate that bilal jenazah training was carried out systematically and integrated into PAI learning using a practice-based approach. Activities included simulations of funeral prayer recitation, understanding Islamic jurisprudence (fiqh) on death, and instilling the values of fardhu kifayah (collective religious obligations). This training has proven effective in improving students’ understanding of the material, fostering empathy, and shaping religious character. The program also received positive responses from students and was supported by collaboration among teachers, the school, and community leaders. The findings indicate that bilal jenazah training is a contextual and effective teaching strategy for strengthening Islamic values in education.Keywords: Bilal Jenazah Training, Implementation, Islamic Education LearningAbstrak: Penelitian ini bertujuan untuk menganalisis tentang implementasi pelatihan bilal jenazah dalam pembelajaran Pendidikan Agama Islam di SMP Negeri 3 Karang Raja. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data meliputi observasi, wawancara mendalam dengan guru PAI dan peserta didik, serta dokumentasi kegiatan keagamaan. Teknik analisis data melalui pengumpulan data, penyajian data, verifikasi dan penarikan kesimpulan. Teknik pemeriksaan keabsahan data melalui triangulasi. Berdasarkan hasil dan pembahasan menunjukkan bahwa pelatihan bilal jenazah dilaksanakan secara sistematis dan terintegrasi dalam pembelajaran PAI dengan pendekatan berbasis praktik. Kegiatan ini mencakup simulasi pembacaan doa jenazah, pemahaman fiqih kematian, dan penanaman nilai fardhu kifayah. Pelatihan ini terbukti mampu meningkatkan pemahaman siswa terhadap materi, menumbuhkan rasa empati, dan membentuk karakter religius. Program ini juga mendapatkan respon positif dari siswa dan didukung oleh kolaborasi antara guru, sekolah, serta tokoh masyarakat. Hasil penelitian ini mengindikasikan bahwa pelatihan bilal jenazah merupakan strategi pembelajaran yang kontekstual dan efektif untuk memperkuat nilai-nilai keislaman dalam dunia pendidikan.Kata Kunci: Implementasi, Pelaltihan Bilal Jenazah, Pembelajaran PAI